Plasmodium falciparum CRK4 directs continuous rounds of DNA replication during schizogony - Ganter, Markus (Nature microbiology, 2017)
Plasmodium parasites, the causative agents of malaria, have evolved a unique cell division cycle in the clinically relevant asexual blood stage of infection1. DNA replication commences approximately halfway through the intracellular development following invasion and parasite growth. The schizont stage is associated with multiple rounds of DNA replication and nuclear division without cytokinesis, resulting in a multinucleated cell. Nuclei divide asynchronously through schizogony, with only the final round of DNA replication and segregation being synchronous and coordinated with daughter cell assembly2,3. However, the control mechanisms for this divergent mode of replication are unknown. Here, we show that the Plasmodium-specific kinase PfCRK4 is a key cell-cycle regulator that orchestrates multiple rounds of DNA replication throughout schizogony in Plasmodium falciparum. PfCRK4 depletion led to a complete block in nuclear division and profoundly inhibited DNA replication. Quantitative phosphoproteomic profiling identified a set of PfCRK4-regulated phosphoproteins with greatest functional similarity to CDK2 substrates, particularly proteins involved in the origin of replication firing. PfCRK4 was required for initial and subsequent rounds of DNA replication during schizogony and, in addition, was essential for development in the mosquito vector. Our results identified an essential S-phase promoting factor of the unconventional P. falciparum cell cycle. PfCRK4 is required for both a prolonged period of the intraerythrocytic stage of Plasmodium infection, as well as for transmission, revealing a broad window for PfCRK4-targeted chemotherapeutics.